Building a Greener Future : The Role of Data Centers in Eco-Friendly Computing - Sudheer Chennuri,; Rajesh Kumar Srirangam,; Vasudev Pendyala, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article explores the critical issue of environmental sustainability in the rapidly evolving landscape of information technology, focusing on the substantial environmental impact of data centers. It delves into innovative strategies and technologies to create more sustainable and eco-friendly computing environments. The article covers key areas such as energy efficiency, renewable energy integration, green cloud computing, edge computing, circular economy practices, and AI-powered optimization. By examining these aspects, the article demonstrates how the IT industry is working to minimize its environmental footprint while meeting the growing demands of our digital world. It highlights not only the environmental benefits of these initiatives but also their economic advantages, showcasing how sustainable practices in computing can lead to significant cost savings and competitive advantages in the market.
Keywords: Data Center Sustainability; Energy Efficiency; Renewable Energy; Green Cloud Computing; E-waste Reduction